PENERAPAN PASAL 6 UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK-POKOK AGRARIA DALAM HUBUNGANNYA DENGAN PEMBANGUNAN DI KAWASAN INDUSTRI - Rusmini Rusmini; Windi Arista (Justici, 2020)
ABSTRACT The implementation of the social function of land rights through land acquisition policies often creates problems in the community. The term "in the public interest" is due to the fact that many land acquisition policies for industrial development are more directed towards facilitating the interests of entrepreneurs. That is, the social function of ownership rights over land becomes more functioning as a means of control over landowners. The application of the principle of social functions of land rights is carried out through a land acquisition policy that must be equipped with a set of laws and regulations as a guarantee of the protection of community rights. The implementation of land acquisition is technically regulated in Law Number 2 of 2012 concerning Land Procurement for Development for Public Interest, Presidential Regulation Number 71 of 2012 concerning Implementation of Land Procurement for Development for Interests, and Head of National Land Agency Regulation Number 5 of 2012 concerning Technical Guidelines for Implementing Land Acquisition.